HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PENGELOLAAN SAMPAH PADAT DI DESA PUJA MULIA KECAMATAN BANDAR KABUPATEN BENER MERIAH - Rika Katiara; Andi Pratama Putra; Nurlaely HS (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACTWaste is a solid material or object that occurs due to human activities that are no longer used, are not liked and are disposed of in a sanitary way, except for those that come from the human body.The purpose of this study is to find out the relationship between knowledge and attitudes towards Solid Waste Management, Bandar District, Bener Meriah Regency in 2024. The design of this study uses Descriptive Analytics with a cross-sectional design of the study. The samplesamples taken were 93 respondents. The sampling technique uses the random sampling technique, which is sampling the entire population. This research has been conducted in Puja Mulia Village, Bandar District, Bener Meriah Regency. on October 21-24, 2024. Based on the results of statistical analysis using the Chi Squer test, the Relationship between Knowledge and Solid Waste Management Behavior in Puja Mulia Village was obtained with a P value = 0.000 < 0.05. There is a Relationship between Attitude and Solid Waste Management Behavior with a P value = 0.005< 0.05. Based on this data, it can be concluded that the better the knowledge and attitude of the community, the better the behavior of solid waste management. Keywords : Knowledge, Attitude, Community Behavior, Waste, Solid Waste Management